Nils Petter Gleditsch: Pioneer in the Analysis of War and Peace (2015)
From an early date, Nils Petter Gleditsch was a well-known person in the Nordic peace research community. He had joined the Peace Research Institute, Oslo (PRIO) in 1964. At that time, as my then fiancée Lena (now wife) and I observed when we arrived in 1967: PRIO had all the enthusiasm of a pioneering environ- ment. I did not meet Nils Petter in his own milieu until a year later. In 1967, he was at one of the centres for peace research at the time: University of Michigan in Ann Arbor. Its Center for Conflict Resolution is often mentioned as one of the early originators of peace research in North America (Wiberg 1988). Certainly this is where the Journal of Conflict Resolution was born, but by this time it was in crisis. Importantly for Nils Petter Gleditsch and for peace research, this was where J. David Singer had just initiated the seminal Correlates of War project. It was exciting in that it used new approaches (systems analysis), new forms of data collection (punch cards!) and new statistical methodologies.